E-050 Effect of general anaesthesia on endovenous pressure measurement during dural sinus stenting for idiopathic intracranial hypertension. (23rd July 2017) - Mekabaty, El; Obusez, E; Chung, C; Luciano, M; Hui, F
Abstract : Introduction: Idiopathic intracranial hypertension (IIH) is a yet not fully understood disease, which is more commonly encountered in obese, young age women. The presence of venous hypertension is often implicated as the pathophysiological origin of IIH, which is postulated to arise as a squeal to intracranial venous stenosis or intrathoracic origin (such as obesity and elevated central venous hypertension). Intracranial venous stenosis has been described in up to 90% of IIH patients. Recently, a case series examined the effect of conscious sedation (CS) and general anesthesia (GA) on endovascular venous pressure gradient measurements. Their results suggest that there is a sizable difference between measurements taken under CS and those under GA, which has an effect on the selection process of IIH patients by either overestimating or underestimating the pressure gradient. In this report, we aim to examine effect of GA of endovascular pressure gradient measurements in IIH patients as well as the decision to go on with stenting. Methods: We performed a retrospective chart review of all patients, who received endovascular transverse sinus stenting due to medical treatment refractory IIH between August 2013 and March 2017 in our institution was performed. Patients who received an endovascular venous pressure measurement during conscious sedation and under general anesthesia in the same setting were then identified. Chart analysis included: patients' demographics; anesthetic agents used in CS and GA; endovenous pressure measurements during CS, GA and after stent placement; stent type and size; and whether the decision to place the stent was revised based on the change in pressure measurements. The threshold for stenting was a pressure gradient across the transverse sinus stenosis of >8 mm Hg. Results: We identified 12 patients who received endovascular pressure gradient measurements under CS and GA. All patients (100%) were female. The mean age was 30.7 years (SD 8.8 and rage 15–42) and the mean BMI was 40.7 (SD 10.1, range 28–63.7). Anesthetic agents used during CS were;; midazolam, fentanyl and propofol and during GA;; propofol and vapor anesthetic (Sevoflurane in 6 patients, Desflurane in 4 patients, and Isoflurane in 2 patients). Mean pressure gradient under CS was 21.7 mmHg (SD 8.5) and 15.8 mmHg (SD 7.9) under GA. Eight (66%) patients showed a pressure gradient reduction after initiation of GA (average 10 mmHg, range 1–20), 2 (18%) patients showed an increase of pressure gradient under GA (2 and 9 mmHg) and 2 (18%) patients had a stable gradient. Post-stenting the pressure gradient was successfully reduced to an average of 2.1 mmHg (SD 2.6). Conclusion: When performed in the same setting, endovascular pressure gradient across transverse stenosis in IIH patients performed under GA shows a sizable reduction (6 mmHg) compared with measurements taken under CS. Further studies are needed to examine the role anesthetic agents and different accompanying factors in regard to the optimal pressure gradient threshold for transverse sinus stenting in IIH patients. Disclosures: A. El Mekabaty: None. E. Obusez: None. C. Chung: None. M. Luciano: None. F. Hui: None.